Factors that influence mothers' prenatal decision to breastfeed in Spain - Ana Ballesta-Castillejos; Juan Gómez-Salgado; Julián Rodríguez-Almagro; Inmaculada Ortiz-Esquinas; Antonio Hernández-Martínez (BMC, 2020)
Abstract Background Parents' decisions about how to feed their newborns are influenced by multiple factors. Our objective was to identify the factors that can influence the decision to breastfeed. Methods Cross-sectional observational online study was conducted in Spain on women who gave birth between 2013 and 2018. The total number of participants was 5671. Data collection was after approval by the ethics committee in 2019. The data were collected retrospectively because the information was obtained from women who were mothers during the years 2013-2018. An online survey was distributed to breastfeeding associations and postpartum groups. Multivariate analysis with binary logistic regression was done to calculate the Adjusted Odds Ratios (aOR). The main result variable was "intention to breastfeed". Results Ninety-seven percent (n = 5531) of women made the decision to breastfeed prior to giving birth. The internet played a role in deciding to breastfeed in 33.7% (n = 2047) of women, while 20.1% (n = 1110) said the same thing about their midwife. We identified five significant factors associated with the mother's prenatal decision to breastfeed: attending maternal education (aOR 2.10; 95% CI 1.32, 3.34), having two (aOR 0.52; 95% CI 0.28, 0.99) and three children (aOR 0.24; 95% CI 0.10, 0.59), previous breastfeeding experience (aOR 6.99; 95% CI 3.46, 14.10), support from partner (aOR 1.58; 95% CI 1.09,2.28) and having a condition during pregnancy (aOR 0.62; 95% CI 0.43, 0.91). Conclusions Factors related with previous breastfeeding experience and education for mothers are decisive when it comes to making the decision to breastfeed. Given the proven influence that partners have in decision-making, it is important for them to be fully involved in the process.